Crucial issues in successful European business - van Luijk, Henk (Journal of business ethics, 1989)
Time has come to put business ethics explicitly on the agenda of those who bear responsibility in the business world and of the scholars working in the field of business administration sciences. Reflection should bear on specific issues of concern, but also on processes of decision in business practices and on patterns of thought at work inside issues and processes. What the issues are, which processes and patterns need scrutiny, is to be decided upon in the course of the public normative debate in which ethicists, as experts of conceptual analysis and argumentation, and corporate executives as experts in decision-making each take an equal and fair share, as people who are able and willing to proffer an argued personal standpoint in an open debate.